Global warming leading to alarming recession of the Arctic sea-ice cover: Insights from remote sensing observations and model reanalysis. Issue 7 (July 2020) - Kumar, Avinash; Yadav, Juhi; Mohan, Rahul
Abstract: The present study quantifies the magnitude of Arctic sea-ice loss in the boreal summer (July–September), especially in September at different timescales (daily, monthly, annual and decadal). The investigation on the accelerated decline in the Arctic sea-ice was performed using different datasets of passive microwave satellite imagery and model reanalysis. Arctic sea-ice declined rapidly in the boreal summer (-10.2 ± 0.8 %decade −1 ) during 1979–2018, while, the highest decline in sea-ice extent (SIE) (i.e., 82, 300 km 2 yr −1 /-12.8 ± 1.1 %decade −1 ) is reported in the month of September. Since late 1979, the SIE recorded the sixth-lowest decline during September 2018 (4.71 million km 2 ). Incidentally, the records of twelve lowest extents in the satellite era occurred in the last twelve years. The loss of SIE and sea-ice concentration (SIC) are attributed to the impacts of land-ocean warming and the northward heat advection into the Arctic Ocean. This has resulted in considerable thinning of sea-ice thickness (SIT) and reduction in the multiyear ice (MYI) for summer 2018. Global and Arctic land-ocean temperatures have increased by ~0.78 °C and ~3.1 °C, respectively, over the past 40 years (1979–2018) while substantial warming rates have been identified in the Arctic Ocean (~3.5 °C in the last 40-year) relative to the Arctic land (~2.8 °C in the last 40-year). The prevailing ocean-atmospheric warming in the Arctic, the SIE, SIC and SIT have reduced, resulting in the decline of the sea-ice volume (SIV) at the rate of -3.0 ± 0.2 (1000 km 3 decade −1 ). Further, it observed that the SIV in September 2018 was three times lower than September 1979. The present study demonstrates the linkages of sea-ice dynamics to ice drifting and accelerated melting due to persistent low pressure, high air-ocean temperatures, supplemented by the coupled ocean-atmospheric forcing. Abstract : Atmospheric science; Environmental science; Earth sciences; Natural hazards; Oceanography; Arctic sea-ice; Global temperature; Sea-ice thickness; Multiyear ice; Climate change